Learning Multiplication by Translating across Microworlds - Sheena Tan; Sean Chorney; Nathalie Sinclair (MDPI AG, 2024)
In this article, we explore students' experiences of using two different digital microworlds of multiplication, which can be found in the multitouch application TouchTimes. We draw on Diagne's notion of translation to frame our study, focusing on the learning that occurs in the movement between the two microworlds. We study translation in terms of actions, strategies, perceptions, and preferences and highlight both the translatables and the untranslatables that emerged in the pair-based interviews that were conducted with grades 3-4 students.